2017
DOI: 10.1111/ans.14020
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic pancreaticoduodenectomy in Brisbane, Australia: an initial experience

Abstract: LPD is a technically challenging operation with a steep learning curve. The early oncological outcomes appear satisfactory. It remains to be determined whether the minimally invasive approach to pancreaticoduodenectomy offers benefits to patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…MIPD involves not only a difficult and complex resection phase but also requires arguably the even more technically demanding reconstruction phase, in particular the creation of a secure pancreato‐enteric anastomoses. Several authors have raised concerns about the potential increase in morbidity and even mortality, especially during the early learning phase. In the study by Kutlu et al , the advantages of LPD, such as shorter hospital stay and lower readmission rate, become apparent only in high‐volume institutions performing more than 25 cases per year .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…MIPD involves not only a difficult and complex resection phase but also requires arguably the even more technically demanding reconstruction phase, in particular the creation of a secure pancreato‐enteric anastomoses. Several authors have raised concerns about the potential increase in morbidity and even mortality, especially during the early learning phase. In the study by Kutlu et al , the advantages of LPD, such as shorter hospital stay and lower readmission rate, become apparent only in high‐volume institutions performing more than 25 cases per year .…”
Section: Discussionmentioning
confidence: 99%
“…However, of even greater concern was that the detrimental effect of lower case volume was exacerbated by the laparoscopic approach . These concerns are especially relevant for institutions in Southeast Asia and the Australasian region whereby truly high‐volume centres such as those in the United States or Korea may not exist . Hence, in order to overcome the large gap between the open and totally MIS approach, many surgeons have proposed the hybrid technique, which has been shown to be a safe approach for surgeons first transitioning from OPD to MIPD .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(25) Real concerns have been raised about the potential increase in morbidity and even mortality, especially during the early learning phase, with several authors having reported a high major morbidity rate during their early learning experience. (8,26) To overcome the large gap between the open and totally laparoscopic approaches, many surgeons have adopted the hybrid technique, which has been shown to be a safe 'in-between' approach for surgeons first embarking on LPD. (10,11,27) The introduction of robotic technology in the early 2000s was one of the greatest advancements for MIS over the past 20 years.…”
Section: Discussionmentioning
confidence: 99%